Combining extracellular matrix hydrogels and electrical stimulation to influence macrophage polarisation - Whitehead, Charlie D. (2024)
The research and development that is invested in the complex process that is wound healing is vast. The volume of wound care research is accelerating in response to skyrocketing costs of complex wound care; ageing populations with increased comorbidities being the significant element. These variables lead to a greater quantity of complex and chronic wounds, which are more costly to treat. One major factor in limiting normal wound repair is persistent inflammation. Macrophages and fibroblasts are crucial regulators of inflammation, amongst other aspects of the wound healing process. In a chronic wound macrophage function has been shown to be impaired, leading to prolonged inflammation; while impacts on fibroblast function have been shown to delay wound closure. Drivers behind these deviations from normal healing are likely due to changes in local stimuli. To address this issue and enhance the treatment of chronic wounds, it becomes imperative to explore innovative strategies aimed at modulating cell function. An expanding field branching into wound care is that of bioelectronic medicine: the fusion of biology and electronics. Electrical stimuli have already been shown to influence migration, phagocytotic activity, and the hastening of wound closure. Electrical stimuli-based therapies are already being used clinically to accelerate wound healing. However, there is a limited understanding about how electrical signals specifically modulate macrophage phenotype, and therefore function. Despite the advancements made in the biological understanding of wound healing and therapies used to treat it, the use of traditional two-dimensional cell culture is still commonly utilised as the first step in the research process. The use of these methods leads to cell morphologies and behaviour that are alien compared to the in vivo equivalent. The application of biomaterials has been utilised to develop a more representative microenvironment. Such models enable cultured cells to better replicate the behaviour that is seen in vivo compared to conventional tissue culture plastic, with biomaterials often offering both structural and biochemical components to augment the in vivo mimetic models. Animal-derived extracellular matrices have been used in for these purposes. In this thesis, it is hypothesised that combining extracellular matrix biomaterials with exogenous electrical stimuli will drive macrophage polarisation towards a pro-healing phenotype. To address this hypothesis, extracellular matrix hydrogels combined with electrical stimuli propagating carbon nanotubes were interrogated for their mechanical and electrical properties. After which, said biomaterials were used in the multi-dimensional culturing of THP-1 derived macrophages and BJ fibroblasts whilst stimulated exogenously with both direct current and electric field effects; with cellular readouts revolving around biocompatibility and cytokine secretion. The incorporation of carbon nanotubes into an extracellular matrix hydrogel generated a novel biomaterial, with softer mechanical and enhanced electrical properties compared to the carbon nanotube free control. The biomaterials generated all proved to be biocompatible, yet the incorporation of carbon nanotubes hindered the acquisition of both qualitative and quantitative data. Regardless, it was shown that the culture of macrophages on the extracellular matrix hydrogels promoted the pro-healing phenotype, as did the stimulation with electric fields. The data posed in this thesis demonstrate the importance of increasing how representative the microenvironment is when it comes to obtaining cellular readouts. Whilst it produces more complex experimental designs with their own challenges, it will allow for a greater confidence in results translated into further in vivo study and beyond.